Uganda : Technical Assistance Report-Strengthening the Performance of Public Investment Management-Next Phase. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Technical Assistance report on the Uganda focuses on strengthening the performance of public investment management - next phase. Significant progress has been achieved since 2015 in strengthening public investment management, with the reforms showing first results. New procedures need to be designed to refresh project information and assess the status of ongoing projects. With better information, a robust prioritization process of ongoing and new projects within the medium-term envelope should be implemented. Discussions with Ministries, Departments and Agencies, and the mission's analysis of the upgraded project data identified inconsistencies between projects' planned use of resources, approved project budgets and the medium-term resource envelope. Reliable and updated information on project forward estimates and commitments like signed contracts and certificates of work is fundamental for ensuring sufficient and timely funding of projects. Recent strengthening of Public Investment Management processes has been accomplished with limited changes to the legal framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet